Development Of Android-Based Edutainment Game Learning Media On Phytagoras Theorem For Junior High School Students - Vera Dewi Susanti; Edy Suprapto; Yuli Anis Wardani (AL-ISHLAH: Jurnal Pendidikan, 2022)
Distance learning during the COVID-19 pandemic caused students' learning motivation to decrease. For this reason, an interesting learning process is needed, one of which is by applying game-based learning.This study aims to develop and determine the feasibility of an Android-based edutainment game learning media on the Pythagorean theorem material for junior high school students. This type of research is Research and Development (RD) using the ADDIE development model, namely Analyze, Design, Development, Implementation, and Evaluation. This research was conducted at MTs Muttaqien PSM Takeran in June 2021. The results of the research on the development of android-based edutainment game learning media include 1) Android-based edutainment game learning media meets the validity criteria with the combined validation average score by the media validator of 84.10% and is included in the fairly valid category, 2) Edutainment game learning media android-based meet the practicality criteria obtained from the average results of filling out student response questionnaires of 87.50% and is included in the very practical category, 3) Android-based edutainment game learning media meets the effectiveness criteria obtained from student learning outcomes tests with a score of N- The gain is 62.32% and is included in the medium category. Thus, it can be concluded that the Android-based edutainment game learning media is feasible to use in learning mathematics on the Pythagorean theorem material. The results of this study provide a contribution in the form of an Android-based edutainment game learning media that is used as an alternative in the learning process.